The purification and utilisation of sewage, with plans of the Croydon irrigation fields - Latham, Baldwin (E. and F.N. Spon, 1867)
This pamphlet describes what has been done to improve the purity of British rivers, and the method of applying liquid sewage to land.
Includes index.
Keywords: Sewage irrigation.; elektronické knihy; electronic books